Signifikansi Usaha Guru Pendidikan Agama Kristen dalam Meningkatkan Gairah Membaca Alkitab pada Siswa Kelas III di Sekolah Dasar Negeri Osiloa - Dina Dimapa; Daeng Salfina Dethan; Petrus Kefas Loka; Yublina Tefa (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Christian Religious Education (PAK) is a divine and human effort carried out systematically and continuously, to transmit knowledge, values, attitudes and skills and behavior that are consistent with the Christian faith. Christian religious education is a joint political activity among pilgrims at a time that deliberately pays attention to God's activities in the present. Thus, it can be said that Christian religious education is very important in transmitting knowledge, values ​​and behavior that are consistent with the Christian faith in realizing the vision of the kingdom of God. According to Andreas, there are 2 research approaches that can be chosen, namely the positivist (quantitative) and naturalist (qualitative) approaches. "Positivist research relies on quantification in collecting and analyzing data to test predetermined hypotheses." Therefore, researchers use a positivist (quantitative) approach. The design used in this research is a survey. A survey is research where the sample is taken from a population with a questionnaire as data collection. The location of the researcher's research was carried out at SD N Osiloa Kupang Tengah for the 2023/2024 academic year, the research period took place from March - May 2023. Based on research conducted by the researcher on the significance of Christian Religious Education (PAK) Teachers' Efforts towards increasing Passion for Reading the Bible in Class III Students At Osiloa State Primary School. The researcher will provide the following conclusions: Based on the research results, it is known that the calculated rs value in the data obtained is greater than the r table. R calculated = 0.999 and r table = 0.684, which means there is a significant relationship between variable There is a significant relationship between variable X: PAK Teacher Effort and variable Y: Students' Passion for Reading the Bible. Judging from the results of calculating the Terminant Coefficient (KP), it is: KP = r² x 100% = 0.647² x 100% = 41.9%. So PAK Teachers' efforts can influence Shiva's Passion for Reading the Bible by 41.9 percent.